THE INFLUENCE OF VITAMIN D ON LUPUS NEPHRITIS ACTIVITY - Kamola M. Daminova; Abdusaid A. Khasanov; Feruza T. Khusankhodjaeva (Central Asian Journal of Medicine, 2025)
The aim of our study was to determine the serum vitamin D levels in patients with lupus nephritis and its association with clinical and laboratory parameters of the disease. Vitamin D levels were studied in patients with systemic lupus erythematosus (SLE) with nephritis, as well as in 20 healthy individuals in the control group. In addition to general clinical examinations, all patients underwent immunological analysis, and the results were compared with vitamin D levels. According to the obtained data, IL-6 and TNF-alpha levels were significantly higher in patients with active lupus nephritis compared to the control group and the group of patients with minimal disease activity. Additionally, IL-4 levels were also elevated in the first group. High IL-6 and TNF-alpha levels were more frequently observed in the group of patients with active lupus nephritis and showed an inverse correlation with vitamin D levels. These findings confirm the strong association between disease activity and vitamin D levels, indicating the need for vitamin D level correction in SLE patients depending on the degree of disease activity.